Prevalence of Toxoplasmosis and Relationships With Estradiol Hormone and Vascular Cells Adhesion Molecular-1(VCAM-1) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sero-epidemiological study were conducted for pregnant and aborted women to investigate the infectionperson with toxoplasmosis in Babylon province during the period from December 2018 till March 2019,ELISA technique for 53 serum samples for pregnant and 67 serum sample for aborted women , according toepidemiological criteria (Residence area , age group , existence of cats in houses , times number of abortionstatus , number of children , collection samples monthly, trimesters period of pregnancy). Concerningbiochemical parameters, the present included determination of estradiol hormone and vascular cell adhesionmolecule -1(VCAM-1) in aborted and healthy women that their ages ranged between 20 to 49 years old. ithas been found a significant increase (P<0.05) in the levels of estradiol hormone in women affected withtoxoplasmosis compared to healthy women .VCAM-1 results indicated a significant increase(P<0.05) ina comparison with those of healthy women it can be concluded that infection with Toxoplasma gondii isassociated with estradiol hormone and vascular cell adhesion molecules.